Simulated textile dye wastewater treatment by electrochemical oxidation: application of response surface methodology (RSM) - Isa, M.H. (Taylor and Francis Inc., 2015)
One of the main problems linked with wastewater from textile industries is colour. Reactive dyes in industrial discharge are difficult to manage as they are not readily amenable to biological treatment. The present study employs an electrochemical method using cast iron electrodes and sodium chloride (NaCl) as electrolyte to decolourize synthetic wastewater containing reactive red dye (Cibacron Red CR). Response surface methodology was employed to assess individual and interactive effects of operational parameters; electrolyte concentration (0.6â1.0Â g/l), current density (1â3Â mA/cm2), reaction time (20â60Â min) and initial dye concentration (20â100Â mg/l) on dye degradation. The range of NaCl concentrations studied did not show any effect on dye removal indicating that the concentrations were higher than the optimum level required. Under optimum process conditions (NaCl concentration 0.6Â g/l, current density 1.4Â mA/cm2 and reaction time 60Â min), initial dye concentration of 100Â mg/l could be almost completely removed (â¥99). Â© 2013, Balaban Desalination Publications. All rights reserved.